Study of energy transfer in polymer blends of TFB:P3HT - Aline Renata Novais Rodrigues; Wesley Renzi; Neusmar Junior Artico Cordeiro; Edson Laureto; Ivan Frederico Lupiano Dias; José Leonil Duarte (Semina: Ciências Exatas e Tecnológicas, 2017)
In order to study the optical properties of TFB polymer and its blend with P3HT polymer, absorption and photoluminescence (PL) measurements were performed for both polymers, and for a blend, TFB: P3HT (95:05), deposited on glass slides using the spin coating technique. Different solvents were used to prepare the samples in order to compare the effects that they might have on the emission and energy transfer between the polymers. Decay time measurements were performed, to find out if this parameter changes in the TFB prepared with different solvents, and also in the presence of P3HT. The photoluminescence measurements of the polymers show no change in the emission of these polymers as we change the solvents used in the preparation of the solutions. However, for the blend there is a change in energy transfer between the polymers depending on the solvent, which shifts the emission color of the sample for the blue or red. On the photoluminescence spectra of the blend an emission in 575 nm, which did not appear in the TFB and P3HT samples is observed. From the decay time measurements, we observed that the 575 nm emission has a long decay time, compatible with the emission by isolated molecules.